2022
DOI: 10.3390/bdcc6020060
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Insurance in California, USA: What Does Community-Generated Big Data Reveal to Us?

Abstract: California has a high seismic hazard, as many historical and recent earthquakes remind us. To deal with potential future damaging earthquakes, a voluntary insurance system for residential properties is in force in the state. However, the insurance penetration rate is quite low. Bearing this in mind, the aim of this article is to ascertain whether Big Data can provide policymakers and stakeholders with useful information in view of future action plans on earthquake coverage. Therefore, we extracted and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Moreover, social media was also used as a tool for communication during flood disasters [21]. In accordance, the study of Gizzi and Potenza [74] showed that in the days immediately following the occurrence of natural hazards such as earthquakes or floods, people rapidly increase online activity in seeking information on preparedness actions. Thus, monitoring online behavior with Big Data can be useful for putting into the field well-timed and geographically targeted information and communication action plans by stakeholders.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, social media was also used as a tool for communication during flood disasters [21]. In accordance, the study of Gizzi and Potenza [74] showed that in the days immediately following the occurrence of natural hazards such as earthquakes or floods, people rapidly increase online activity in seeking information on preparedness actions. Thus, monitoring online behavior with Big Data can be useful for putting into the field well-timed and geographically targeted information and communication action plans by stakeholders.…”
Section: Discussionmentioning
confidence: 93%
“…Search engine trends serve as a tool that can identify, both through real-time surveillance and temporal analysis (periods), the needs and interests of the population in relation to health information (and information related to other fields) [12,28]. In this regard, it is important to note that this study encompasses an analysis of ecological data and, therefore, the findings may not be representative at the individual level, both owing to the study design and the tool's limitations [64].…”
Section: Limitationsmentioning
confidence: 99%
“…GT has been used to explore a wide range of topics in the health field [12] and has proven to be particularly useful in the early detection of health events such as diabetes [16] or obesity [17,18]. In addition, GT has also been shown to be very useful when it comes to studying population behaviors, and there are studies in the field of diet [19], occupational health [20,21], bariatric surgery [22], home care [23], gout [24], sexually transmitted diseases [7,25,26], as well as public health monitoring of disease outbreaks [27], among other research fields [28]. A review by Mavragani et al [12] showed that these studies generally focus on examining seasonality, correlations, estimation models, and, to a lesser extent, provide predictions and forecasts.…”
Section: Introductionmentioning
confidence: 99%